The Relationships between Service Quality, Reputation, and Performance in Hospitality - Magnus Haukur Asgeirsson; Thorhallur Gudlaugsson; Gunnar Thór Jóhannesson (Tourism and Hospitality, 2024)
The importance of service quality and a positive reputation, individually leading to enhanced performance of hospitality organizations, is undisputed. However, little is known about their interplay and how they collectively explain the variability in performance. The purpose of this article is to contribute to the understanding of the individual and collective impact of service quality and reputation on variability in performance, categorized as customer satisfaction and loyalty. This study was conducted using quantitative research methods with data derived from hotel guests in Iceland in the summer of 2023. We gathered 1487 valid answers from guests staying at any of the 9 selected hotels, all belonging to the same Icelandic chain. The factor analysis revealed a credible four-factor model that consists of tangible service, performed service, reputation, and performance. All three independent factors had a statistically positive connection with variabilities in performance, and the collective explanation ratio for the model was strong. The independent factors were correlated to a satisfactory level, and tangible service had the strongest unique connection to performance.